Abolition - Davis, Angela Y. (Hamish Hamilton, an imprint fo Penguin Books, 2024)
From trailblazing political activist Angela Y. Davis, a major new collection of essays and interviews that argue for a radical rethinking of our prison systemsAn icon of revolutionary politics, Angela Y. Davis has been at the forefront of collective movements for prison abolition for over fifty years. Abolition: Politics, Practices, Promises, the first of two important new volumes, brings together an essential collection of Davis s essays, conversations, and interviews over the years, showing how her thinking has sharpened and evolved even as she has remained uncompromising in her commitment to collective liberation.Davis traces a genealogy of the penal system, from slavery to the prison industrial complex, offering a trenchant analysis of the relationship between the prison system and capitalism, both in the US and on a global scale. Combining decades of analytical brilliance and lessons from organising both inside and beyond prison walls, Davis addresses the history of abolitionist practice, details the unique contributions of women to abolitionist struggles, and offers the radical tools we need for revolutionary change.Powerful and rewarding, filled with insight and provocation, Abolition: Politics, Practices, Promises, is essential reading for anyone seeking to imagine a world without prisons. A woman of undeniable courage. She should be heard New York Times She has eyes in the back of our head. With her we can survive and resist John Berger Behold the heart and mind of Angela Davis: open, relentless, and on time! She is as radiant, she is as true, as that invincible sunrise June Jordan